2021
DOI: 10.1186/s12874-021-01268-z
|View full text |Cite
|
Sign up to set email alerts
|

Shifting research culture to address the mismatch between where trials recruit and where populations with the most disease live: a qualitative study

Abstract: Background Research participation is beneficial to patients, clinicians and healthcare services. There is currently poor alignment between UK clinical research activity and local prevalence of disease. The National Institute of Health Research is keen to encourage chief investigators (CIs) to base their research activity in areas of high patient need, to support equity, efficiency and capacity building. We explored how CIs choose sites for their trials and suggest ways to encourage them to recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…While a policy priority in many countries, 53,54 socioeconomic factors may not always be a top priority for researchers who design and evaluate (weight management) interventions. A recent qualitative study found that although trial Chief Investigators deemed matters relating to equity to be important, the majority were primarily motivated by a commitment to delivering successful trials efficiently 113 . Undertaking trials in less research‐active sites, with higher disease prevalence and lower socioeconomic status, could be seen as a risk to trial success 113 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While a policy priority in many countries, 53,54 socioeconomic factors may not always be a top priority for researchers who design and evaluate (weight management) interventions. A recent qualitative study found that although trial Chief Investigators deemed matters relating to equity to be important, the majority were primarily motivated by a commitment to delivering successful trials efficiently 113 . Undertaking trials in less research‐active sites, with higher disease prevalence and lower socioeconomic status, could be seen as a risk to trial success 113 .…”
Section: Discussionmentioning
confidence: 99%
“… 113 Undertaking trials in less research‐active sites, with higher disease prevalence and lower socioeconomic status, could be seen as a risk to trial success. 113 In the current review, this may be reflected by the majority ( n = 20) of trials making no specific mention of the socioeconomic profile of their study sample in relation to strengths or limitations. Moreover, this could also point to the need for a shift in the way that researchers report on the socioeconomic profiles of study samples, and how this information is contextualized in relation to intervention reach, trial outcomes, and the potential for interventions to positively (or negatively) impact health inequalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach is to promote equity in innovation through reason-based interventions, such as distributing research activity closer to the populations it serves 8 . But any intervention here is in as much need of empirical evidence as the novel treatments research aims to discover.…”
Section: Introductionmentioning
confidence: 99%